Utilization of Sludge from the Sulianti Saroso Hospital Wastewater Treatment Plant as Compost Material - Anggraeni, Yeyen; Febrina, Laila; Mulyawati, Ira; Pratiwi, Tiara Zakiyah; Maemun, Siti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Hospital activities generate by-products from the treatment of liquid waste, namely sludge that settles in sedimentation tanks. The sludge produced thus far has been transported by a third party in collaboration with the hospital. This study was conducted to utilize hospital wastewater treatment plant (WWTP) sludge with the aim of determining the moisture content, carbon (C) content, nitrogen (N) content, and C/N ratio in the raw WWTP sludge before and after composting compared to SNI 19-7030-2004 standards. Additionally, the study aimed to identify the average differences in each variation of WWTP sludge and rice husk composition. This research employed an experimental method. The composting process was conducted aerobically with the following variations: 95% WWTP sludge:5% rice husk (A1), 85% WWTP sludge:15% rice husk (A2), 75% WWTP sludge:25% rice husk (A3), and 65% WWTP sludge:35% rice husk (A4), with the addition of EM4 activator 55 ml + 90 ml sugar solution diluted to 300 ml. The preliminary test results for the WWTP sludge showed a moisture content of 68.76%, C content of 28.00%, N content of 14.32%, and C/N ratio of 1.95. From the results of the ANOVA statistical test and Post Hoc Duncan test, it was found that the average variation in WWTP sludge: rice husk composition had a significant difference, with the ideal composition being variation A1 (95% WWTP sludge:5% rice husk).